PECULIARITIES OF DENTAL STATUS IN ADOLESCENTS AFFECTED WITH ALCOHOL DEPENDENCE - Skrypnikov, A.N.; Sheshukova, O.V.; Kazakov, A.A.; Trufanova, V.P.; Kazakova, E.S. (World of Medicine and Biology, 2018)
The article identifies the features of the dental status in adolescents affected with alcohol dependence. Due to the chronic action of ethanol against the background of low circulation, we observed an increase in the incidence and intensity of MTM lesions in patients. The lack of qualified dental care in patients with alcohol dependence leads, as the results of the study showed, to the aggravation of oral lesions clinical symptoms, an increase in their intensity and severity. The problem is aggravated by the progredient course of the underlying disease, due to the incessant negative influence of factors, which led to the occurrence of the oral cavity diseases.
Keywords: acute and chronic MTM injuries; mechanical trauma to the MTM; the negative impact of ethanol on the MTM